Changes in spring-mass model parameters and energy cost during track running to exhaustion - Slawinski, J.; Heubert, R.; Quievre, J.; Billat, V.; Hannon, C. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this study was to determine whether exhaustion modifies the stiffness characteristics, as defined in the spring-mass model, during track running. We also investigated whether stiffer runners are also the most economical. Nine well-trained runners performed an exhaustive exercise over 2000 meters on an indoor track. This exhaustive exercise was preceded by a warm-up and was followed by an active recovery. Throughout all the exercises, the energy cost of running (Cr) was measured. Vertical and leg stiffness was measured with a force plate (Kvert and Kleg, respectively) integrated into the track. The results show that Cr increases significantly after the 2000-meter run (0.192 ± 0.006 to 0.217 ± 0.013 mL·kg-1·m-1). However, Kvert and Kleg remained constant (32.52 ± 6.42 to 32.59 ± 5.48 and 11.12 ± 2.76 to 11.14 ± 2.48 kN·m-1, respectively). An inverse correlation was observed between Cr and Kleg, but only during the 2000-meter exercise (r = -0.67; P <= 0.05). During the warm-up or the recovery, Cr and Kleg, were not correlated (r = 0.354; P = 0.82 and r = 0.21; P = 0.59, respectively). On track, exhaustion induced by a 2000-meter run has no effect on Kleg or Kvert. The inverse correlation was only observed between Cr and Kleg during the 2000-meter run and not before or after the exercise, suggesting that the stiffness of the runner may be not associated with the Cr.